Dynamic nature of SecA and its associated proteins in Escherichia coli - Adachi, Shun; Murakawa, Yasuhiro; Hiraga, Sota (Frontiers in Microbiology, 2015)
Mechanical properties such as physical constraint and pushing of chromosomes are thought to be important for chromosome segregation in Escherichia coli and it could be mediated by a hypothetical molecular “tether”. However, the actual tether that mediates these features is not known. We previously described that SecA (Secretory A) and SecY, components of the membrane protein translocation machinery, and AcpP (Acyl carrier protein P) were involved in chromosome segregation and homeostasis of DNA topology. In the present work we performed three-dimensional deconvolution of microscopic images and time-lapse experiments of these proteins together with MukB and DNA topoisomerases, and found that these proteins embraced the structures of tortuous nucleoids with condensed regions. Notably, SecA, SecY and AcpP dynamically localized in cells, which was interdependent on each other requiring the ATPase activity of SecA. Our findings imply that the membrane protein translocation machinery plays a role in the maintenance of proper chromosome partitioning, possibly through “tethering” of MukB (a functional homolog of structural maintenance of chromosomes [SMC] proteins), DNA gyrase, DNA topoisomerase IV and SeqA (Sequestration A).